Evaluation of Nanoemulsion of Eucalyptus globulus Oil as Potent Botanical Larvicide Against Malaria Vector , Anopheles stephensi and West Nile Vector, Culex pipiens Under Laboratory and Semi-field Conditions - Sara Sabzalizade; Amir Amani; Hassan Vatandoost; Fatemeh Hosseini; Roya Najafi-Taher; Hamid Reza Basseri (Tehran University of Medical Sciences, 2022)
Objectives Due to undesired environmental impact of insecticides as well as resistant of vectors to them, development of organic and natural insecticides have been more considered. In the current study, we developed nanoemulsion of eucalyptus and investigated lavicidal activity of it against malaria vector, Anopheles stephensi and Culex pipiens under  laboratory as well as semi field conditions.  Materials and Methods: An optimized nanoemulsion was prepared by mixing Eucalyptus oil, Tween 80 and ethanol at ratio of 1:2:1.5 in distilled water, then, stirred for 20 minute at room temperature. The product was then used for bioassay tests against 3-4th instar larvae of Anopheles stephensi as well as Culex pipiens.  Furthermore, semi field trial was carried out to evaluate larvicidal activity of nanoemulsion of eucalyptus. Results: Nanoemulsion of eucalyptus showed significantly high lavicidal activity comparing with bulk eucalyptus essential oil. The LC50 and LC90 value of nanoemulsion against An. stephensi were 111.0 and 180.8 ppm respectively and 29.5 and 73.7 ppm for Cx.  pipiens, respectively. In the semi field condition, the Nanoemulsion of eucalyptus decreased 1-2nd instar larval density of Culicines and Anophelines to 90.1%  and 85.2%, respectively. Conclusion: The nano formulation of eucalyptus oil showed high larvicidal activity.  Therefore, nanoemulsion of eucalyptus oil can be used as an eco-friendly larvicide against mosquitoes.